Distribution of β-amyloid and pTau in brain cortex depending on age and mental state - Alexandra V. Sentyabreva; Olyesya A. Vasyukova; Yana A. Zorkina; Alisa V. Andryuschenko; Georgy P. Kostyuk; Irina Z. Eremina; Anna M. Kosyreva (RUDN Journal of Medicine)
Relevance. Alzheimer’s disease (AD) is the most cause of disability and dementia, which is the 7th leading cause of death worldwide. Diagnosis of AD includes detection of amyloid plaques and hyperphosphorylated tau protein (pTau) in the brain. However, in recent years the amyloid hypothesis of AD development has been criticized and revised, and a growing pool of data emerges indicating more complex pathogenetic mechanisms leading to neurodegeneration in AD. The aim of our work was to evaluate the presence and distribution of amyloid plaques and pTau fragments in different regions of the cerebral cortex in patients 60 years old with diagnosed dementia and without cognitive impairment, as well as in people 60 years old. Materials and Methods. The amount of β-amyloid and pTau fragments in three groups of patients was measured on IHC stained histological sections in the regions of parahippocampal, temporal, and occipital cortex. Results and Discussion. Amyloid plaques were detected in all patients over 60 years of age (with and without dementia), while in younger individuals 60 years of age they were found in 66% of cases. The largest amyloid-β burden was observed in the occipital cortex. pTau was detected in all cortical areas in the three groups of patients. Also, the amount of pTau was higher in the occipital cortex in patients over 60 years of age both with and without dementia than in the group of people under 60 years of age. Conclusion. Thus, accumulation of pTau occurs earlier than β-amyloid. The amount of pTau was higher in patients over 60 years of age with clinically manifested dementia, while in some regions the amount of amyloid conglomerates is higher in cognitively intact patients. The findings point to much more complex mechanisms of the neurodegenerative diseases development with the formation of amyloid plaques being a consequence rather than cause of the disease.